A Mini-Open, Dorsal Approach for Scaphoid Fracture Fixation With a Ligament Sparing Arthrotomy. Issue 1 (March 2020) - Dodds, Seth D.; Rush, Augustus J.; Staggers, Jackson R.
Abstract : There are several surgical approaches that are currently used to address nondisplaced scaphoid waist fractures, including percutaneous fixation, limited exposure fixation, and traditional open techniques through a volar or dorsal approach. Although percutaneous fixation has some theoretical advantages, it is much more difficult to achieve an accurate starting point for a headless compression screw. The purpose of this paper is to describe a simple, dorsal, mini-open approach to the scaphoid that minimizes incision size, extensor tendon dissection, capsular trauma, and vascular disruption, while still allowing for direct visualization of the proximal pole and optimal exposure for accurate screw placement. As a case report, we retrospectively evaluated 80 consecutive patients with closed scaphoid fractures. There were 2 groups, with 44 patients (age: 24±10 y) receiving a percutaneous dorsal approach and 36 patients (age: 30±16 y) treated with a mini-open approach. All scaphoid fractures were acute or fibrous nonunions (<6 mo from injury, except for one) treated with cannulated headless compression screws. Intraoperative and postoperative complications were measured and evaluated for each group to assess for differences between the percutaneous approach and the mini-open technique. We found no significant difference in complication rate with the mini-open dorsal technique compared with the dorsal percutaneous approach (8.3% vs. 4.5%, respectively). Therefore, we suggest consideration of this mini-open dorsal approach for scaphoid fracture fixation as a useful and safe technique.